The Effectiveness of Infant Massage to Increase in Baby Weight in Bpm Inawati - Inawati Inawati; Nur Sitiyaroh (Risenologi, 2022)
One of the factors in increasing the growth and development of babies is to provide stimulation. Baby massage has many benefits, one of which is increasing the baby's weight, that's because babies who are massaged will experience an increase in vagus nerve tone (10th brain nerve) which will cause an increase in levels of gastrin and insulin absorption enzymes, thus food absorption will increase. getting better which is why the weight of babies who are massaged will increase more than those who are not massaged. Data obtained from BPM Inawati, infants who were given massage from 0-3 months of age had weight gain > 140 grams per week, but there were still many babies who were never given massage. Objective : Knowing the effectiveness of baby massage on increasing baby's weight. The method was Quasi experimental with pretest posttest research type with Control Group Design. The sample in this study was all babies born at BPM Inawati in November-December 2021 as many as 30 people, the sampling technique was the total sample. The results shows that the average baby weight before baby massage was done in the intervention group was 3,276.67 grams and in the control group was 3,511.67 grams. The average baby weight after baby massage in the intervention group was 5,922.33 grams and in the control group was 5,114.33 grams. There is an effectiveness of baby massage on increasing baby's weight (p.value 0.000). The conclusions and suggestions show there is an effectiveness of baby massage on increasing baby's weight (p.value 0.000). It is hoped that health workers, especially midwives, will provide baby massage training for postpartum mothers to do baby massage themselves at home.